2022
DOI: 10.3390/land11081125
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Soil Type in Triggering Shallow Landslides in the Alps (Lombardy, Northern Italy)

Abstract: Shallow landslides due to the soil saturation induced by intense rainfall events are very common in northern Italy, particularly in the Alps and Prealps. They are usually triggered during heavy rainstorms, causing severe damage to property, and sometimes causing casualties. A historical study and analysis of shallow landslides and mud-debris flows triggered by rainfall events in Lombardy was carried out for the period of 1911–2010, over an area of 14,019 km2. In this study, intensity–duration rainfall threshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…It follows that the prediction and mitigation of such phenomena are highly important. Although the analyses of physically based models (PBMs) are more reliable, PBMs are mainly adopted in susceptibility assessment [38,72], being statistical approaches based on rainfall thresholds predominant in regional Landslide Early Warning Systems (LEWS) [25][26][27][28]. The results of this study have shown that SLIP, i.e., simplified PBMs implemented in the X-SLIP platform, can provide accurate real-time predictions when the stability analyses integrate rainfall forecasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It follows that the prediction and mitigation of such phenomena are highly important. Although the analyses of physically based models (PBMs) are more reliable, PBMs are mainly adopted in susceptibility assessment [38,72], being statistical approaches based on rainfall thresholds predominant in regional Landslide Early Warning Systems (LEWS) [25][26][27][28]. The results of this study have shown that SLIP, i.e., simplified PBMs implemented in the X-SLIP platform, can provide accurate real-time predictions when the stability analyses integrate rainfall forecasts.…”
Section: Discussionmentioning
confidence: 99%
“…Most regional LEWS provide space-time information via data-driven methods, e.g., based on rainfall thresholds (empirical relationships between rainfall and landslide occur-rence derived from past events) [25][26][27][28] or on artificial intelligence [29][30][31][32][33]. The mentioned methods are applied for real-time predictions thanks to the rain forecast.…”
Section: Introductionmentioning
confidence: 99%
“…Average slope is ~ 46%. The thin, clay-loamy soil 41 is a leptic and eutric Cambisol 42 , 43 . We sampled trees one month after the wildfire (December 2017), in May, July, and October of 2018, and in July 2019.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the Zemun settlement on the northern outskirts of Belgrade has experienced a number of landslides in the last three decades, endangering buildings and roads [2]. Shallow landslides due to the soil saturation induced by intense rainfall events are very common in northern Italy, particularly in the Alps and Prealps [3]. How to reduce the huge losses caused by landslide disasters and ensure the safety of disaster relief personnel is an urgent problem to be solved.…”
Section: Introductionmentioning
confidence: 99%